Zastosowanie osiągnięć neuronauki w procesie wspomagania rehabilitacji osób z niepełnosprawnością – przykładowe badania - Zielińska, Jolanta (Kultura-Społeczeństwo-Edukacja, 2023)
The article presents the issue of nervous systems and the neural correlate of information processing in the contextof the application of research results in this area in the process of supporting the rehabilitation of people with disabilities. The currently dynamically developing science of the borderland called “neuroscience” was presented, which is a great opportunity for special pedagogy to appear in its system, especially in the area of issues related to diagnosis and rehabilitation. The aim was to answer the question: What cognitive and research inspirations result from supporting the rehabilitation of people with disabilities with the achievements of neuroscience? The application of its achievements in the rehabilitation of people with disabilities has a complementary task, supporting an effective rehabilitation process in its practical dimension. The concept of a damaged brain of a disabled person was presented as a very general and imprecise one, resulting from diseases, injuries or developmental disorders, but which fundamentally affects the functioning of various areas of the brain, causing various symptoms and functional disorders. The essential and original part of the article is based on the latest literature on the subject, a review of the results of research on the brain work of people with various types of disabilities, made with the use of neuroimaging techniques. The concept of neuroplasticity was discussed in the context of obtaining an answer to the question: Can a damaged brain repair itself and how? By restoring, not bypassing, damaged or destroyed neural pathways. In conclusion, it was indicated that the intended effect of the discussed research is to create theoretical and empirical foundations for developing models of the functional architecture of the brain of a person with a specific type of disability, taking into account their individual capabilities, needs and even interests.